Resident Empowerment and National Park Governance: A Case Study of Three-River-Source National Park, China - Yulian Ma; Yaolong Li; Yonghuan Ma; Yusong Liu; Xuechun Li; Fanglei Zhong (Land, 2025)
The underlying tension between national park development and local community interests presents a significant challenge for contemporary ecological governance. Resident empowerment (RE) is increasingly recognized as a crucial pathway to mitigate this tension and achieve effective national park governance (NPG). However, the intrinsic mechanisms through which RE influences NPG have not been thoroughly explored in existing research. Drawing on the practice of government–resident interaction in China’s national parks, this paper investigates how the decentralization of power can balance the dual goals of environmental protection and social development. Using Three-River-Source National Park as a case study, we employ an ordered Logit regression model to examine the impact of RE on NPG. The study finds that RE is significantly and positively associated with NPG. Its influence is primarily mediated through three mechanisms: an identity effect (enhancing community belonging), an income effect (improving livelihood capabilities), and an environmental effect (strengthening participation in and perception of ecological conservation). Based on this empirical analysis, we recommend policies that further expand residents’ decision-making and management rights and broaden participation channels, thereby promoting the sustainable development and social equity of NPG.